2003
DOI: 10.1046/j.1464-5491.2003.00887.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial factors and diabetes‐related outcomes following diagnosis of Type 1 diabetes in adults: The Edinburgh Prospective Diabetes Study

Abstract: Long-standing psychosocial factors have a significant influence on self-reported outcomes during the 12 months following diagnosis of Type 1 diabetes but may not be reliable predictors of glycaemic control. Further follow-up is necessary to determine the longer-term predictors of objective (e.g. glycaemic control) and subjective (e.g. quality of life) indicators of coping in people with diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(58 citation statements)
references
References 46 publications
(65 reference statements)
3
55
0
Order By: Relevance
“…1. Tables 1 and 2, and the Electronic supplementary material (ESM Table 1), detail the papers that were included in (n=14) [27][28][29][30][31][32][33][34][35][36][37][38][39][40] and excluded from (n=11) the review. There were 16 relationships between psychosocial measures and disease-related factors in populations with diabetes and six relationships between psychosocial measures and diseaserelated factors in populations without diabetes at baseline.…”
Section: Resultsmentioning
confidence: 99%
“…1. Tables 1 and 2, and the Electronic supplementary material (ESM Table 1), detail the papers that were included in (n=14) [27][28][29][30][31][32][33][34][35][36][37][38][39][40] and excluded from (n=11) the review. There were 16 relationships between psychosocial measures and disease-related factors in populations with diabetes and six relationships between psychosocial measures and diseaserelated factors in populations without diabetes at baseline.…”
Section: Resultsmentioning
confidence: 99%
“…The 12-month follow-up rate for HbA 1c was 88% (n = 305). The median age was 36 years [interquartile range (IQR) [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43][44]; duration of diabetes was 18 years (IQR 11-25); and HbA 1c was 9.4% (IQR 8.8-10.2). The adjusted mean 12-month HbA 1c was 0.45% lower in those treated with MET + CBT [95% confidence interval (CI) 0.16% to 0.79%, p = 0.008] than for usual care; 0.16% lower in those treated with MET (95% CI 0.20% to 0.51%, p = 0.38) than for usual care; and 0.30% lower with MET + CBT than with MET (95% CI -0.07% to 0.66%, p = 0.11).…”
Section: Resultsmentioning
confidence: 99%
“…28 In 84 newly diagnosed adults with type 1 diabetes alcohol consumption and knowledge of diabetes at 4 months after diagnosis were found to be independent predictors of glycaemic control at 12 months, explaining 16% of the variance. 29 Other factors such as the General Health Questionnaire, diabetes-specific quality of life, cognitive ability and personality were not but these findings may reflect the short follow-up.…”
Section: Factors Associated With Suboptimal Glycaemic Controlmentioning
confidence: 96%
“…42, 43 The demographic and psychosocial characteristics explored in this study showed minimal explanatory power in terms of glycaemic control, which may reflect the strength of the intervention and that people will derive benefit whatever their background characteristics. However, the results do suggest that screening people before participating in diabetes structured education programmes to select those who are more likely to gain the most in terms of improvements in glycaemic control is unwarranted, particularly if current demographic and psychosocial characteristics are used.…”
Section: Qualitative and Quantitative Evaluation Of The Dafne Intervementioning
confidence: 99%
“…Relatively few studies have identified determinants of either glycaemic control or QoL in adults with type 1 diabetes as most research in this area has focused on childhood and adolescence or on type 2 diabetes. 42,43 To our knowledge, only one study to date has examined determinants of glycaemic control after diabetes structured education. 42 Although the outcomes of diabetes structured education programmes are relatively consistent across studies, 6,7,38,44,45 it remains unclear which elements of these programmes are critical to success or whether specific patient characteristics or experiences predict those with optimal and suboptimal outcomes.…”
Section: 34mentioning
confidence: 99%